Pesan-Pesan Dakwah dalam Adat Melengkan pada Upacara Pernikahan Suku Gayo Kabupaten Aceh Tengah - Arifin Zain; Reza Muttaqin; Fauzi Fauzi; Maturidi Maturidi (Alhadharah: Jurnal Ilmu Dakwah, 2021)
There is a traditional guide called melengkan in the Gayo wedding ceremony. Melengkan is a traditional speech that certain people can only deliver. This study raises the issue of da'wah messages in the melengkan at the wedding ceremony. This study aims to find out and find answers to the formulation of research problems: the messages of da'wah contained in the melengkan tradition, the usefulness of the melengkan, and what factors affect the delivery of the message of melengkan in the Gayo tribal wedding ceremony. The research uses a qualitative approach to the method. Data was collected through observation, interviews, and documentation studies. The data processing and analysis technique was carried out in three steps: data reduction, data display, and conclusion drawing/verification. The results showed that the messages of da'wah contained in the melengkan tradition at the wedding ceremony were in the form of bonds of friendship between fellow human beings, glorifying guests, glorifying temple experts, maintaining marital relations, reminding to remain devoted to both parents, directing husband and wife to become sakinah mawaddah warahmah family